HUBUNGAN TINGKAT PENGETAHUAN TENTANG MAKANAN CEPAT SAJI DENGAN POLA KONSUMSINYA PADA MAHASISWA TINGKAT II AKPER PANTI KOSALA SURAKARTA - Budi Santoso; Viona Velania (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2017)
Fast food is type of food that prepared and served quickly so it does not take along time to consume. This food is very popular with young people. Most of thenutritional contents, including high-calorie, high-fat / cholesterol, high in salt andlow in fiber, have an impact on obesity and other long-term health risks. Students(year II) of the Academy of Nursing (AKPER) Panti Kosala Surakarta asrespondents in this study, their average age: 19.68 year-old. The pattern of foodconsumption is influenced typically by the behavior of the teenagers, often theireating times were not regularly and prefer to dine outdoors with friends.This analytic study with cross sectional approach aims to analyze the correlationof the level of their knowledge about fast food and their consumption pattern atthe 103 year II students (female: 80 and male :23) AKPER Panti KosalaSurakarta as respondents (population: 138 students).Results of this study were presented in frequency distribution tables and thecorrelation between variables were analyzed using Pearson correlation test withÎ± = 5% (0.05). The results show there is no significant correlation (p = 0.441)between the level of knowledge and fast food consumption patterns at the year IIstudents of AKPER Panti Kosala Surakarta.Keywords: fast food, level of knowledge, consumption pattern